Factores de riesgo obstétrico asociados a hemorragia postparto inmediato en gestantes atendidas en el Hospital Alfredo Noboa Montenegro Guaranda- Bolívar, enero-junio 2019 - Revello Silva, Mayra Alejandra (2019)
Background: Postpartum hemorrhage worldwide is one of the main causes of maternal death, the majority occur in developing countries, being in Ecuador the second cause, which has been implemented by the guide of the Ministry of Public Health to reduce the maternal morbidity. Objectives: To determine the Obstetric Risk factors associated with immediate postpartum hemorrhage in pregnant women treated at the Alfredo Noboa Montenegro hospital, January-June 2019 period. Method: the research is descriptive, retrospective, non-experimental, the study includes a universe of 625 patients, which applied the inclusion and exclusion criteria, resulting in 53 users diagnosed with immediate postpartum hemorrhage at the Alfredo Noboa Montenegro Hospital during the period January - June 2019. Results: the results obtained through the analysis of the medical records, the main risk factors for immediate postpartum hemorrhage that presented with the highest incidence were highlighted regarding the study problem: multiparity (58%), prenatal control deficit (53%), anemia (53%), age> 30 years (51%), home birth care (45%), preeclampsia (38%) In the same way, the causes of postpartum hemorrhage that they presented were atony (42%), retention of coronary remains (36%). Conclusions: This work aims to know the main obstetric risk factors that are associated with immediate postpartum hemorrhage in pregnant women treated at the Alfredo Noboa Montenegro hospital in the period January-June 2019 with the purpose of preventing maternal morbidity and mortality